Development and Validation of the Italian “Brief Five-Item Chronic Pain Questionnaire” for Epidemiological Studies - Toccaceli V; Tenti M; Stazi MA; Fagnani C; Medda E; Gargiulo L; Burgio A; Sampaolo L; Ferri M; Raffaeli W (Journal of Pain Research, 2022)
Virgilia Toccaceli,1 Michael Tenti,2 Maria Antonietta Stazi,1 Corrado Fagnani,1 Emanuela Medda,1 Lidia Gargiulo,3 Alessandra Burgio,3 Letizia Sampaolo,4 Maurizio Ferri,1 William Raffaeli2 1Centre for Behavioural Sciences and Mental Health, Istituto Superiore di Sanità (Italian National Institute of Health), Rome, Italy; 2Fondazione ISAL, Institute for Research on Pain, Torre Pedrera, Italy; 3ISTAT, National Institute of Statistics, Rome, Italy; 4Centre for Disease Prevention and Health Promotion, Istituto Superiore di Sanità (Italian National Institute of Health), Rome, ItalyCorrespondence: Michael Tenti, Fondazione ISAL, Via San Salvador, 204, Rimini, 47922, Italy, Tel +390541725166, Fax +390541725164, Email michael.tenti@fondazioneisal.itBackground: Chronic pain (CP) prevalence estimates addressing a wide phenotype are still quite fragmented and may vary widely due to the lack of standardized tools of investigation. There is an urgent need to update general population CP estimates.Methods: For this purpose, the Brief Five-item Chronic Pain Questionnaire was developed through experts’ consultations for design and content validity assessment; literature analysis of measures used to investigate CP for general population surveys; understandability evaluation through a survey on a convenience sample of affected and non-affected individuals; reliability assessment by means of two double-wave online surveys carried out by the Italian Twin Registry; criterion and construct validity assessment through the third wave of the 2019 European Health Interview Survey (Ehis).Results: Key dimensions were defined to describe CP main aspects from a public health perspective. Literature analysis showed that validated questionnaires were rarely used to address important public health CP aspects. Understandability of the measure was good. Test-retest analyses showed adequate reliability of the measure: k values were at least “moderate” with highest values regarding CP “occurrence” and “intensity”. Correlations of CP with well-known comorbidities (cancer, depression), and specific traits (age, education) as well as of CP and its intensity with “physical pain occurrence and intensity” detected in the Ehis 2019, confirmed, respectively, a good construct and criterion validity. Construct validity was also evaluated through the correlation between “perceived treatment effectiveness” and “interference of pain in daily life activities” as recorded in the Ehis 2019.Conclusion: The designed questionnaire is a brief self-administered measure, particularly suitable to detect persistent states of pain and related intensity in large-scale general population surveys by means of a first filtering item followed by four further items. It is, in fact, designed to detect CP possible underlying causes/triggers, drugs/treatments taking and frequency, and self-perceived effectiveness among CP sufferers. Further validation of the measure in different social and cultural contexts is desirable.Keywords: chronic pain, epidemiology, methodology, questionnaire, survey, European Health Interview Survey